2023
DOI: 10.1021/acschemneuro.2c00370
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Fluctuations of Orexin-A and -B in Cynomolgus Monkey Cerebrospinal Fluid Determined by a Novel Analytical Method Using Antiadsorptive Additive Treatment Followed by Nanoflow Liquid ChromatographyHigh-Resolution Mass Spectrometry

Abstract: Orexin-A (OXA) and -B (OXB) are involved in the regulation of multiple physiological functions including the sleep–wake states; therefore, it is critical to monitor their levels under various conditions. Unfortunately, the widely used radioimmunoassay has insufficient specificity for OXA. Although liquid chromatography–tandem mass spectrometry (LC–MS/MS) has higher specificity for OXA, previously reported OXA levels in human cerebrospinal fluid (CSF) measured using this technique are still inconsistent. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…OX-A and orexin B are neuropeptides released from lateral hypothalamic orexin neurons that regulate multiple physiological functions including wakefulness by neuronal excitation 19 , 27 . As conventional radioimmunoassay methods to measure OX-A have poor selectivity for OX-A, we established a novel, accurate method using nanoflow liquid chromatography–high-resolution mass spectrometry (nanoLC-HRMS) 28 . Evaluation of diurnal fluctuation of OX-A in monkey cisternal CSF using this method revealed that OX-A levels gradually increased during the active period, reached a maximum at the end of the active period, then dropped to the trough level of the sleep period within 2 h 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OX-A and orexin B are neuropeptides released from lateral hypothalamic orexin neurons that regulate multiple physiological functions including wakefulness by neuronal excitation 19 , 27 . As conventional radioimmunoassay methods to measure OX-A have poor selectivity for OX-A, we established a novel, accurate method using nanoflow liquid chromatography–high-resolution mass spectrometry (nanoLC-HRMS) 28 . Evaluation of diurnal fluctuation of OX-A in monkey cisternal CSF using this method revealed that OX-A levels gradually increased during the active period, reached a maximum at the end of the active period, then dropped to the trough level of the sleep period within 2 h 28 .…”
Section: Discussionmentioning
confidence: 99%
“…As conventional radioimmunoassay methods to measure OX-A have poor selectivity for OX-A, we established a novel, accurate method using nanoflow liquid chromatography–high-resolution mass spectrometry (nanoLC-HRMS) 28 . Evaluation of diurnal fluctuation of OX-A in monkey cisternal CSF using this method revealed that OX-A levels gradually increased during the active period, reached a maximum at the end of the active period, then dropped to the trough level of the sleep period within 2 h 28 . Although the sleep/wake structure of monkeys and rodents is different (monkeys have a monophasic structure while rodents have a polyphasic structure), the diurnal fluctuation pattern of OX-A may be similar to that of Aβ 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The original orexin measurements were performed using antibodies and are thus somewhat uncertain, given that these antibodies may possibly also detect the parent peptide PPO, orexin-A fragments or altogether different molecules (VI. ), but measurements with mass spectrometry-based methods or biosensors, which are not subject to these liabilities, have also recently confirmed the diurnal rhythmicity of orexin release (Hopkins et al, 2021;Duffet et al, 2022a;Narita et al, 2023).…”
mentioning
confidence: 87%
“…Non-radioactive heavy labels ( 13 C, 15 N) have been used in custom-made internal orexin-A and -B standards for mass spectrometry-based detection assays (VI.) (Hirtz et al, 2016;Bårdsen et al, 2019;Lindström et al, 2021;Hopkins et al, 2021;Ball et al, 2023;Narita et al, 2023) and in NMR (III.A., V.A.). A caged version of orexin-Bthat can be uncaged upon a UV or near-UV light pulsehas recently been developed (Duffet et al, 2022b).…”
Section: Labeled and Other Types Of Special Ligandsmentioning
confidence: 98%
“…However, during REM sleep, the activity of orexin neurons decreases, resulting in a reduction of orexin release. Interestingly, recent studies in primates have clearly shown that the highest concentrations of orexin are recorded until just after the monkeys go to sleep and then falling through the night and reaching the lowest concentrations around wake time [11,12]. Then, orexin concentrations start rise linearly.…”
Section: The Role Of Orexin In Rem Sleep Regulationmentioning
confidence: 99%